2022
DOI: 10.1186/s12913-022-08118-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in medication reconciliation interventions between six hospitals: a mixed method study

Abstract: Background Although medication reconciliation (MedRec) is mandated and effective in decreasing preventable medication errors during transition of care, hospitals implement MedRec differently. Objective Quantitatively compare the number and type of MedRec interventions between hospitals upon admission and discharge, followed by a qualitative analysis on potential reasons for differences. Methods This ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Suboptimal medication leads to impaired ADL and reduced QOL, and to unnecessary neuropsychiatric symptoms. Collaboration between pharmacists and physicians during all stages of the rehabilitation process therefore is required and beneficial [68,69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suboptimal medication leads to impaired ADL and reduced QOL, and to unnecessary neuropsychiatric symptoms. Collaboration between pharmacists and physicians during all stages of the rehabilitation process therefore is required and beneficial [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…The 6 moderate grade studies permit some conclusions, which might benefit the field. The only long-term controlled multidisciplinary study [47] clearly showed that a focused inpatient program including medication optimization [69], followed by an intensive outpatient program, was able to keep PwPD stable for 2 years, whereas a matched control group all stayed in the nursing home. This means that focused PD rehabilitation, including medication optimization with advanced therapies like L-dopa-and apomorphine infusions if indicated, is able to postpone definite nursing home admission with years, resulting in a huge improvement of ADL and with a significant cost reduction at the same time.…”
Section: Discussionmentioning
confidence: 99%